2008
DOI: 10.1159/000121372
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Heartburn in Patients with Gastroesophageal Reflux Disease under Routine Care

Abstract: Background: Gastroesophageal reflux disease (GERD) is a common disorder. The aim of our study was to describe the prevalence of nighttime heartburn and its associations with esophagitis, Barrett’s esophagus, and extra-esophageal symptoms. Methods: Data were collected as part of the ongoing Progression of Gastroesophageal Reflux Disease (ProGERD) study. Based on endoscopy results, patients were categorized as having nonerosive GERD, erosive GERD, or Barrett’s esophagus. ORs and 95% CIs derived from logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The ProGERD study is a prospective, multi‐centre, open cohort study, in which patients with GERD are being followed up after treatment with esomeprazole 12–24 . Briefly, the patients from the ProGERD study were divided as follows: NERD, n = 2853 (no erosions, no endoscopic or histological BO); Los Angeles (LA) AB, n = 2256 (LA A or B, no BO), LA CD, n = 404 (ERD according to LA classification, no BO); and BO (endoscopic and histological diagnosis of BO), n = 305 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ProGERD study is a prospective, multi‐centre, open cohort study, in which patients with GERD are being followed up after treatment with esomeprazole 12–24 . Briefly, the patients from the ProGERD study were divided as follows: NERD, n = 2853 (no erosions, no endoscopic or histological BO); Los Angeles (LA) AB, n = 2256 (LA A or B, no BO), LA CD, n = 404 (ERD according to LA classification, no BO); and BO (endoscopic and histological diagnosis of BO), n = 305 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients were eligible for the ProGERD study if they were at least 18 years of age, reported heartburn as their main symptom and were referred for esophagogastroduodenoscopy (EGD) because of reflux symptoms. Details of recording of the general and medical history have been published previously 12–24 . Exclusion criteria were: history of gastrointestinal surgery and/or gastro‐oesophageal malignancies; continuous treatment with any acid‐suppressive drug for more than 7 days within the last 4 weeks prior to inclusion; contraindications to esomeprazole treatment; any ‘alarm symptoms’ of malignancy or other significant cardiovascular, pulmonary (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Night-time heartburn is common in GERD patients and is associated with reduced well-being. [18][19][20] A Gallup survey, for example, found that subjects with nocturnal symptoms had impaired daytime functioning. 20 Accordingly, frequent nocturnal symptoms among patients with GERD are associated with a loss in work productivity.…”
Section: Discussionmentioning
confidence: 99%
“…[53] Moreover, almost 50% of patients with known GORD report nocturnal heartburn under the routine clinical care provided by their GPs. [54] Nocturnal symptomatic gastro-oesophageal reflux can lead to difficulty in getting to sleep and remaining asleep, and to daytime fatigue and impaired work productivity. Polysomnography reveals, in particular, brief wake phases and shortening of the second sleep phase.…”
Section: Sleep Disordersmentioning
confidence: 99%